Life Expectancy and Parental Education - Mathias Huebener (Institute of Labor Economics (IZA), 2019)
This study analyses the relationship between life expectancy and parental education. It extends the previous literature that focused mostly on the relationship between individuals' own education and their life expectancy. Based on data from the German Socio-Economic Panel Study and survival analysis models, we show that maternal education is related to children's life expectancy - even after controlling for children's own level of education. This applies equally to women and men as well as to further life expectancies examined at age 35 to age 65. This pattern is more pronounced for younger cohorts. In most cases, the education of the father is not significantly related to children's life expectancy. The vocational training and the occupational position of the parents in childhood, which both correlate with household income, cannot explain the link. Children's health behaviour and the health accumulated over the life course appear as important channels. The findings imply that the link between education and life expectancy is substantially stronger and that returns to education are higher if intergenerational links are considered.
Keywords: I12; I14; I26; 330; health inequality; returns to education; mortality; parental background; human capital; survival analysis